Relying on their own hands: Examining the causes and consequences of supermarket decentralization in Detroit. Issue 7 (9th August 2022) - LeDoux, Timothy F.; Vojnovic, Igor
ABSTRACT: This paper examines the historical evolution of uneven neighborhood food environments in tri-County Detroit, Michigan from 1970 to 2010. It demonstrates how broader economic conditions and business decisions not germane to the region interacted with a landscape marked by economic polarization and racial segregation to create an uneven food environment where Black neighborhoods disproportionately bore the brunt of restrictive food access. It also contextualizes capital-centric accounts of retail decentralization by showing how underlying inequities in the region limited how Detroit's Black community could respond to store closures in their neighborhoods as well as their ability to relocate closer to suburban stores. This work raises questions about policies that heavily subsidize national and regional supermarket chains to relocate to urban centers as well as policies that solely focus on supply factors rather than the broader inequities remaking the region.